(untitled) (Journal of actual problems of jurisprudence, 2018)
The article is devoted to study the essence of the legal nature of the procedural form of execution of the confession of guilt in committing a criminal offence. The article discusses the concept of transaction plea. The conclusion is that the Institute deals plea needs further research. Key words: criminal trial, plea bargain, the bodies of pre-trial investigation.